Creating and distribution process of graphic design portfolio for a bachelor student - Denisova, Alexandra; Khabirova, Maja; Phung, Hyu Nghia; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
The main purpose of this bachelor thesis is to show a complete process of creating a graphic design portfolio including a theoretical overview of design and graphic design itself, creativity and design processes. Furthermore implementing obtained knowledges in real life outputs. It also demonstrates the importance of portfolio as a critical element for every designer. The theoretical part is mainly focused on explaining the design process as the most important part of creating any kind of design materials and also general value of portfolio. The practical part is focused on the implementing knowledge of those stages and also trying out tools and techniques which are typically used in the creative process, covering the whole process of making a complete portfolio and its distribution as well.
Vedoucí práce: Maja Khabirova
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses